Analisis Visual Kemasan Kue Gabin Samarinda Untuk Pengembangan Desain Kemasan - Hidayanto, Andi Farid; Atmono, Yohanes Firananta Setyo (Meraki: Journal of Creative Industries, 2023)
Heritage typical traditional food is the region typical food that is different from those from other regions. In carrying it, the food needs a container in the form of packaging. As a souvenir, the packaging needs to have a uniqueness that can differentiate it from other packages and at the same time can show its identity. One of the difference comes from the attributes of the packaging from the visual side. Because the visual appearance is the first thing that catch the costumers attention and also influences purchasing decisions. So it needs to be analyzed what attributes are required from the visual side. This is a qualitative reasearch. Preliminary data were obtained from a literature study on food packaging design which was analyzed for its attributes, the results were qualitativeized using the NVivo application. NVivo is used to illustrate the decision analysis results framework by coding the data according to the classification scheme. The result of this study is the arrangement of the visual attributes of traditional food packaging, which will be applied to develop the packaging design for the Samarinda gabin biscuit, to reconstruct the packaging which is suitable to current taste without losing its original identity.